RADI-04. COMBINED RADIOLOGICAL, PATHOLOGICAL AND MOLECULAR OUTCOME EVALUATION IN NEWLY DIAGNOSED NON-BRAINSTEM PEDIATRIC HIGH-GRADE GLIOMA FROM THE RANDOMIZED, MULTICENTER HERBY PHASE II TRIAL. Issue 2 (22nd June 2018) - Jaspan, Tim; Morgan, Paul; Rodriguez, Daniel; Warren, Daniel; Warmuth-Metz, Monika; Aliaga, Esther Sanchez; Calmon, Raphael; Jones, Chris; Mackay, Alan; Varlet, Pascale; Hargrave, Darren; Canete, Adela; et al.
Abstract: INTRODUCTION: The HERBY trial assessed the efficacy of adding Bevacizumab (BEV) to postoperative radiotherapy/temozolamide (RT/TMZ) in children with newly diagnosed non-pontine high-grade gliomas (HGG). The trial showed no difference in OS or EFS between BEV and non-BEV treatment arms. METHODS: Radiological, pathological and molecular data were evaluated to characterise pediatric HGG and correlate with outcome measures. RESULTS: 74/124 (59.7%) patients had Cerebral hemispheric and 50/124 (40.3%) Midline tumors. Pathological diagnosis was available in all cases (111 astrocytomas /124), molecular data in 89/124. K27M histone mutations were present in 24/33 Midline cases with molecular data, and G34R/V mutations in 7 Cerebral cases. 116 patients completed treatment (RT/TMZ=56, BEV=60). 54/70 (77%) Cerebral cases underwent total/near-total resection with debulking/biopsy in 16/70 (23%). Fewer (12/46) Midline tumors had total/near-total resections than debulking/biopsy (34/46) (p<0.001). Leptomeningeal (LMM) dissemination occurred more frequently in patients with Midline (17/46) than Cerebral tumors (10/70)(p=0.003). Mean OS (14.27 months) and EFS (9.63) in Midline tumors were significantly lower than mean OS (20.72) and EFS (14.93) in Cerebral tumors (p=0.007, p=0.009). LMM occurred in 9/24 (38%) K27M and 17/57(29%) WT patients, 11/116 (9%) BEV and 16/116 (14%) RT/TMZ cases. Pseudoprogression occurred in 10/116 (9%) cases (RT/TMZ arm=8, Bev arm=2; p=0.017), with no relationship to mutation subtype. CONCLUSION: K27M mutations, fewer total/near total tumor resections, more frequent leptomeningeal spread and shorter OS/EFS characterizes Midline pediatric HGG. Pseudoprogression occurred less in BEV than in TMZ/RT treated patients, suggesting BEV supresses the treatment response to RT/TMZ therapy, replicating findings in adult populations.